Beyond Clinical Examination: Utilizing MRI Surveillance to Detect Recurrence of Soft Tissue Sarcomas and Differentiate from Posttherapeutic Changes - Felix R. M. Koenig; Alfred H. Kielburg; Snehansh Roy Chaudhary; Christian Wassipaul; Akash Ganguly; Raoul Varga; Martin L. Watzenboeck; Iris-Melanie Noebauer-Huhmann (Biomedicines, 2024)
Background: Early detection of soft tissue sarcoma (STS) recurrence is essential; however, the role and timeline of Magnetic resonance imaging (MRI) surveillance are still under debate. The aim of this study was to determine whether local recurrence (LR) could be identified via clinical examination alone and to assess the MRI morphology of primary STS and LR. Methods: This retrospective study included all patients with STS recurrence after surveillance for at least five years from the tumor database of the Medical University of Vienna from 2000 until December 2023. The characteristics of primary STS and LR and the time interval to recurrence and clinical detectability were assessed. The MRIs of LR and posttherapeutic changes (PTC) were compared with the initial MRIs. Results: A total of 57 patients (60% male; mean age 58.5 ± 18.0 years) with STS and histologically confirmed LR were included. The mean time interval to LR was 2.3 ± 1.8 years (range 108 to 3037 days). The clinically detectable recurrences were significantly larger than the inapparent ones (71.9 cm3 vs. 7.0 cm3; p < 0.01). The MRI morphology of all LRs (26/26) closely resembled the initial STS. For comparison, nine patients were included with clinically suspected LRs, which were histologically proven to be PTC. None of these resembled the primary STS. Conclusion: Based on clinical symptoms alone, especially small and early recurrences can be missed, which supports the importance of MRI surveillance.